Legal Reform of Corporate Criminal Liability Model in the National Criminal Code - Herlina Manullang; Martono Anggusti; Debora; Binsar Manogu Tua (Journal of Law, Politic and Humanities, 2025)
The National Criminal Code's Criminal Law Reform governs criminal offences perpetrated by, for, and on behalf of the Corporation. Concerning Article 48 of the National Criminal Code, the framework of corporate criminal liability has embraced three models: the Corporation as maker and responsible entity, management as maker and responsible party, and the Corporation as both maker and accountable entity. Simultaneously, imposing fines, supplementary punishments, and sanctions within the National Criminal Code exemplifies utilitarian philosophy, integrating distributive and commutative justice. The practical perspective assesses punishment based on its advantages or utility; in this instance, the punishment aims to deter corporations from engaging in similar actions in the future